Mental health literacy of Chinese nurses from public general and psychiatric hospitals: a cross-sectional study - Wang, Anni; Jia, Shoumei; Shi, Zhongying; Sun, Xiaoming; Zhu, Yuan; Shen, Miaoli; Tang, Dayu; Chen, Xizhu (Frontiers in Psychiatry, 2023)
Background Mental health literacy (MHL) is crucial to address issues related to mental illness. Nurses’ MHL is even more important because they are expected to deal with both the physical and psychological consequences of mental disorders. Objective This study investigated the level, discrepancy, and characteristics of MHL among Chinese nurses from both public general and psychiatric hospitals; identified influential factors; and explored the relationship between MHL and mental health status. Methods Using a stratified cluster sampling method to select participants, a cross-sectional survey was conducted to describe the MHL of 777 nurses from 13 general and 12 psychiatric hospitals using the Chinese version of the Mental Health Literacy Scale, Patient Health Questionnaire-2, Generalized Anxiety Disorder-2, and a demographic questionnaire. A multiple regression analysis was used to determine the factors influencing MHL among the nurses recruited. Results The participants’ total score on the Chinese version of the Mental Health Literacy Scale was 93.25 (SD = 10.52). Multiple regression analysis revealed that nurses who worked in psychiatric or higher-level hospitals, with higher professional titles or higher education had higher levels of overall MHL and core MHL, while those working in general hospitals, with shorter work duration, or who were unmarried had higher social acceptance of patients. Nurses’ MHL was closely correlated with their mental health status. Conclusion The overall and core MHL of Chinese nurses were at a moderate level, with social acceptance remaining at a relatively low level. There is an urgent need for MHL promotion programs to improve the MHL of clinical nurses. The focus must be given to overall MHL, especially core MHL, for non-psychiatric nurses to enhance their competence in mental health promotion and identification; more emphasis should be placed on the social acceptance of patients with mental illnesses for psychiatric nurses to improve their provision of professional services. Better MHL would be a formula for improving nurses’ own mental health and their mental health service competence.